EPIDEMIOLOGICAL PROFILE OF PATIENTS HOSPITALIZED IN A NEONATAL INTENSIVE CARE UNIT - de Souza, Maryana Neves (2018)
The infant mortality (IM) is caused due to a combination of biological, cultural, social events and flaws in the health system. In Brazil, it´s possible to observe that the control of IM is not yet evident. This study aimed to identify the main causes of hospitalization in a Neonatal Intensive Care Unit in 2012 and stratify their characteristics. This was a documentary cross-sectional observational study. 393 medical records were analyzed by the discharge neonatal summary and official data of deaths, made from January 2012 to December of 2012. The data were tabulated with the program “Originlab data analysis” and formatted in the Excel program. Prematurity was the main cause of hospitalization and neonatal death identified at work. Low birth weight, gestational age less than 34 weeks and the length of hospital stay were also analyzed characteristics favoring an increases risk of death. Efforts to better stratification of data from national epidemiological profiles are important for better attention to this age group.